2020
DOI: 10.1002/agj2.20126
|View full text |Cite
|
Sign up to set email alerts
|

Time‐based remote sensing yield estimates of cotton in water‐limiting environments

Abstract: The use of high-throughput phenotyping aids breeding programs in making more informed selections and advancements. This study's objectives were to determine which proximal remote sensing parameters (normalized difference red edge [NDRE], normalized difference vegetation index [NDVI], difference between canopy and air temperatures [∆T], and plant height) are robust estimators of cotton lint yield and to use a time-integrated function of one parameter as a single phenotypic measurement for predicting yield. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…In a recent study, Thompson et al. (2020) reported the greatest correlations between NDVI, NDRE, T c − T a , and cotton lint yield in side‐by‐side comparisons that we were able to find in the literature. Peak correlations with lint yield reached nearly .8 in one year, depending on the parameter, though correlations were substantially lower in the other, drier season.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…In a recent study, Thompson et al. (2020) reported the greatest correlations between NDVI, NDRE, T c − T a , and cotton lint yield in side‐by‐side comparisons that we were able to find in the literature. Peak correlations with lint yield reached nearly .8 in one year, depending on the parameter, though correlations were substantially lower in the other, drier season.…”
Section: Introductionsupporting
confidence: 55%
“…As discussed earlier, broadscale analysis across multiple growing conditions widens the variation in yield responses and leads to better correlations (Arnall et al, 2016;Jiang et al, 2018;Plant et al, 2000; but does not inform on how accurately high-throughput measures can predict lint yield in side-by-side comparisons of cotton germplasm grown in the same conditions. Thompson et al (2020) reported the greatest correlations between NDVI, NDRE, T c − T a , and cotton lint yield that we were able to find in the literature in comparisons of cotton germplasm grown in the same conditions. Peak correlations ranged from about .5 to almost .8 in one year, depending on the parameter, and trends in the rise and fall of R 2 over time were apparent, but correlations were substantially lower in a relatively dry year.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Remote sensing approaches allow for data collection on much larger studies encompassing a wide genetic diversity in order to phenotype for abiotic stress resilience. Remote sensing has been utilized for a variety of purposes such as measuring canopy height ( Varela et al , 2017 ; Thompson et al ., 2018 , 2020 ; Zhou et al , 2020 ), biomass ( Neumann et al , 2015 ; Padilla-Chacón et al , 2019 ), canopy temperature ( Romano et al , 2011 ; Pauli et al , 2016 ; Graß et al , 2020 ), and leaf area ( Neilson et al , 2015 ; Zhang et al , 2019 ), and predicting yield ( Rischbeck et al , 2016 ; Becker and Schmidhalter, 2017 ; El-Hendawy et al , 2017 ; Zhou et al , 2020 ). Through the use of specialized vegetation indices (VIs) or spectral bands alone, remote sensing can quickly and efficiently collect data on different traits simultaneously, non-destructively, and with a high spatio-temporal frequency.…”
Section: Introductionmentioning
confidence: 99%